Greek art in motion : studies in honour of Sir John Boardman on the occasion of his 90th birthday - Morais, Rui,; Leão, Delfim Ferreira,; Rodríguez Pérez, Diana,; Ferreira, Daniela,; Boardman, John, 1927- (Archaeopress archaeology., 2019)
Over 50 papers, first presented at the international congress 'Greek Art in Motion' (Lisbon, 2017) in honour of Sir John Boardman's 90th Birthday, are collected here under the following headings: Sculpture, Architecture, Terracotta & Metal, Greek Pottery, Coins, Greek History & Archaeology, Greeks Overseas, Reception & Collecting, Art & Myth.